Prospects for locally produced nutrient-dense rice in Liberia: How import preferences and agronomic traits shape consumer demand and farmer adoption - Twine, Edgar E.; Arouna, Aminou; Aboudou, R.; Ndindeng, Sali Atanga (2025)
This study examines whether Liberian consumers are willing to pay for new, locally produced nutrient-dense rice, and if farmers are willing to grow such rice. Further, the study investigates the role of preferences for imported rice and agronomic traits, respectively, in relation to willingness to pay and willingness to grow new nutrient-dense rice in Liberia. Contingent valuation surveys were conducted of 543 rice consumers and 557 farmers, and linear regression and logistic models were applied to the data. Ninety-one percent of rice consumers were willing to buy nutrient-dense rice and pay a price premium of 8% on average. Consumers who prefer imported rice to local rice are willing to pay less for locally produced nutrient-dense rice than those who do not. Ninety-two percent of rice farmers were willing to grow nutrient-dense rice varieties. Preference for yield reduces the odds of growing nutrient-dense rice. These results have implications for introducing nutrient-dense rice varieties in Liberia.